Species Composition, Structural Patterns, and Environmental Drivers of a Low-Diversity Mangrove Ecosystem in Toima Village, Banggai, Indonesia - Siti Aisyah Marjuno; Moh. Fahri Haruna; Fredik Falentino Suboong; Suci in Zahra (Universitas Labuhanbatu, 2026)
Background: Mangrove ecosystems are increasingly threatened by land-use change, coastal development, and other anthropogenic disturbances that can reduce biodiversity and impair ecosystem functions. Recent information, species composition and vegetation structure in Toima Village remains limited. This study aimed to analyze species composition, vegetation structure, and environmental factors associated with the mangrove ecosystem in Toima Village, Banggai Regency. Methodology: Data were collected using purposive sampling approach combined with line-transect plots at 2 sampling stations, comprising 9 plots representing seedling, sapling, and tree growth stages. Vegetation analyses included the Important Value Index (IVI), Shannon–Wiener diversity index (H’), evenness index (E), dominance index (C), and environmental parameters. Findings: The results revealed that the mangrove community consisted of only 3 species: Rhizophora apiculata, Sonneratia alba, and Sonneratia caseolaris. Species diversity was low across all growth stages (H’= 0.84–0.89), whereas Evenness was relatively high (E= 0.76–0.81). S. caseolaris exhibited the highest IVI values, reaching 134.36% at the tree stage, 179.41% at the sapling stage, and 128.67% at the seedling stage, indicating strong dominance and regeneration capacity. Environmental conditions supported mangrove growth, with salinity ranging from 23–24 ppt, temperatures around 30°C, and neutral pH levels. However, differences in substrate characteristics, with mixed mud–sand substrates supporting better mangrove growth than predominantly sandy substrates. Anthropogenic activities, particularly port development and land conversion, were associated with reduced mangrove diversity in the Toima area. Contribution: These findings highlight the importance of substrate heterogeneity and species-specific adaptive capacity in shaping mangrove community structure within low-diversity ecosystems and provide a scientific basis for locally adapted mangrove conservation, management, and restoration strategies